GROWING EXCLUSION OF THE MAJORITY: The “Triumph of Wahhabism” and Its Threat to Indonesian Islam in the Democratic Society (State Islamic University (UIN) of Sunan Ampel Surabaya, 2023)
Although Wahhabi institutions have neither grown rapidly nor attracted a significant number of followers in Indonesia, the spread of Wahhabist thoughts among Indonesian Muslims has outreached the institutions and their propagators. This study proves the argument by examining the rift among a Muslim community in the Eastern Java village of